α-stable interference modeling and cauchy receiver for an IR-UWB Ad Hoc network - Ghannudi, Hamza El; Clavier, Laurent; Azzaoui, Nourddine; Septier, Francois; Rolland, Paul-alain (IEEE transactions on communications, 2010)
In this paper we investigate ad hoc networks based on impulse radio ultra wideband. Due to multiple access, the interference distribution is not Gaussian. One important reason for errors is the presence of close interferers generating pulse collision. However such events are rare and we propose an α-stable model compatible with this fact due to its heavy tailed distribution. We derive the analytical expression of the two significant parameters. They depend on the attenuation coefficient, the users' density, the pulse collision probability and the pulse shape. We finally propose receiver strategies (Cauchy receiver and p-norm) that outperforms the classical Gaussian receiver.